Calcium phosphate bioceramics: From cell behavior to chemical-physical properties - Magnaudeix, Amandine (Frontiers in Biomaterials Science, 2022)
Calcium phosphate ceramics, including hydroxyapatite (HA), have been used as bone substitutes for more than 40 years. Their chemical composition, close to that of the bone mineral, confers them good biological and physical properties. However, they are not sufficient to meet all the needs in bone regenerative medicine, such as in the context of critical bone lesions. Therefore, it is essential to improve their biological performances in order to extend their application domains. In this aim, three approaches are mainly followed on the assumption that the biological response can be tuned by modifications of the chemical physical properties of the ceramic: 1) Incorporation of specific chemical species into the calcium phosphate crystalline lattice of chemical elements to stimulate bone repair. 2) Modulation of the bioceramic architecture to optimize the cellular responses at the interface. 3) Functionalization of the bioceramic surface with bioactive molecules. These approaches are supposed to act on separate parameters but, as they are implemented during different steps of the ceramic processing route, they cannot be considered as exclusive. They will ineluctably induces changes of several other physical chemical properties of the final ceramic that may also affect the biological response. Using examples of recent works from our laboratory, the present paper aims to describe how biology can be affected by the bioceramics modifications according to each one of these approaches. It shows that linking biological and chemical physical data in a rational way makes it possible to identify pertinent parameters and related processing levers to target a desired biological response and then more precisely tune the biological performance of ceramic biomaterials. This highlights the importance of integrating the biological evaluation into the heart of the processes used to manufacture optimized biomaterials.